Removal of a Solitary Synovial Chondromatosis of the Temporomandibular Joint Using Arthroscopy - Pastore, Gabriel Pires [UNESP]; Goulart, Douglas Rangel [UNESP]; Pastore, Patricia Radaic [UNESP]; Prati, Alexandre Javaroni [UNESP] (Lippincott Williams & Wilkins, 2016)
The diagnosis of synovial chrondromatosis of temporomandibular joint (TMJ) requires a combined assessment consisting of clinical, radiologic, and histopathologic examinations. The purpose of this study is to report in 1 patient the removal of a single large cartilaginous nodule floating in the upper joint compartment using arthroscopy. A 30-year-old woman was referred to our department complaining about pain in preauricular area and restricted mouth opening. Imaging of magnetic resonance reveals anterior disc displacement and right joint effusion. Arthroscopy of TMJ was performed for diagnosis and treatment. During the arthroscopy a large loose body was identified and removed with a biopsy forceps; lavage was conducted with ringer solution. Hyaluronic acid was injected in TMJ at surgery, 1 and 3 months after surgery. Postoperative magnetic resonance imaging showed articular disc on position and no effusion. The patient was followed up of 1 year without sign and symptoms. Arthroscopic procedure of TMJ was effective in diagnosis and removal of a solitary loose body of synovial chrondromatosis. Viscosupplementation appers to offer benefits in controlling pain and functional improvements.
Keywords: Arthroscopic surgery; magnetic resonance imaging; synovial chondromatosis; temporomandibular joint disorders; temporomandibular joint